Advanced Electronic Circuits Principles, Architectures and Applications on Emerging Technologies - Niu, Mingbo (IntechOpen, 2018)
This research book volume offers an important learning opportunity with insights into a variety of emerging electronic circuit aspects, such as new materials, energy harvesting architectures, and compressive sensing technique. Advanced circuit technologies are extremely powerful and developed rapidly. They change industry. They change lives. And we know they can change the world. The exhibition on these new and exciting topics will benefit readers in related fields.